2006
DOI: 10.1007/s10096-006-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a macrolide to a ß-lactam in bacteremic pneumococcal pneumonia

Abstract: In the study presented here, data collected prospectively from 340 adult patients hospitalised in five countries with bacteremic pneumococcal CAP and treated with a ss-lactam +/- a macrolide were analysed retrospectively to evaluate the efficacy of this antimicrobial combination. Univariate and multivariate analyses revealed no significant effect on case fatality rate when a macrolide/ss-lactam regimen was used as initial therapy. Results were not affected by severity of illness, or by excluding patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 18 publications
0
30
1
Order By: Relevance
“…It is not clear if any specific combination of agents is most effective, but most studies have examined the efficacy of combining an extended-spectrum cephalosporin and a macrolide (4,11,16,31,33,42). Conversely, several studies have refuted the advantages of combination therapy over monotherapy for severe CAP (5,13,19). Data comparing the outcomes of the two most frequently recommended empirical antibiotic regimens for CAP (dual therapy with an extended-spectrum ␤-lactam and a macrolide or montherapy with an antipneumococcal quinolone) for patients with severe CAP are sparse.…”
mentioning
confidence: 99%
“…It is not clear if any specific combination of agents is most effective, but most studies have examined the efficacy of combining an extended-spectrum cephalosporin and a macrolide (4,11,16,31,33,42). Conversely, several studies have refuted the advantages of combination therapy over monotherapy for severe CAP (5,13,19). Data comparing the outcomes of the two most frequently recommended empirical antibiotic regimens for CAP (dual therapy with an extended-spectrum ␤-lactam and a macrolide or montherapy with an antipneumococcal quinolone) for patients with severe CAP are sparse.…”
mentioning
confidence: 99%
“…However, outcome comparisons were adjusted most commonly to risk factors for mortality, not identical to the risk factors for the treatment regimen. Studies that showed similar characteristics for patients receiving monotherapy and combination therapy, or adjusting for the differences observed between the groups, showed no differences in outcomes [26][27][28]. The authors believe that differences between study groups similar to those in the present cohort might have existed in former studies, and were not captured because the propensity for prescribing monotherapy versus combination therapy was not investigated.…”
Section: Discussionmentioning
confidence: 64%
“…Few studies showed no effect [25][26][27][28]. Some features of these studies are described in table 4; most studies were retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…In several retrospective or nonrandomized prospective clinical studies, a survival benefit has been shown in patients with pneumococcal CAP treated with a combination of b-lactam antibiotics and macrolides compared with those treated with b-lactam monotherapy [61][62][63][64][65]. However, two large prospective cohort studies showed no difference between these two regimens [66,67]. In a retrospective study in patients with severe sepsis owing to pneumonia caused by any microorganism, macrolide use was associated with decreased mortality, even in patients with macrolideresistant pathogens [68].…”
Section: Macrolide Antibioticsmentioning
confidence: 99%